2023
DOI: 10.3390/bios13040419
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Microfluidic Chip Powered by EWOD for In Vitro Manipulation of Bovine Embryos

Abstract: Digital microfluidics (DMF) holds great potential for the alleviation of laboratory procedures in assisted reproductive technologies (ARTs). The electrowetting on dielectric (EWOD) technology provides dynamic culture conditions in vitro that may better mimic the natural embryo microenvironment. Thus far, EWOD microdevices have been proposed for in vitro gamete and embryo handling in mice and for analyzing the human embryo secretome. This article presents the development of the first microfluidic chip utilizing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 94 publications
0
1
0
Order By: Relevance
“…These methods often involve micro and nanofabrication techniques (M.J. Lopez-Martinez & E.M. Campo, 2011). One innovative approach, which utilizes electrowetting-on-dielectric technology, is the creation of microfluidic chips that are capable of manipulating bovine embryos in vitro (Karcz et al, 2023). By integrating nanotechnology with various other fields, researchers have developed unique nanomaterials that can revolutionize diagnostic and therapeutic applications (Barhoum et al, 2022).…”
Section: Nanomaterials In Embryo Manipulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…These methods often involve micro and nanofabrication techniques (M.J. Lopez-Martinez & E.M. Campo, 2011). One innovative approach, which utilizes electrowetting-on-dielectric technology, is the creation of microfluidic chips that are capable of manipulating bovine embryos in vitro (Karcz et al, 2023). By integrating nanotechnology with various other fields, researchers have developed unique nanomaterials that can revolutionize diagnostic and therapeutic applications (Barhoum et al, 2022).…”
Section: Nanomaterials In Embryo Manipulationsmentioning
confidence: 99%
“…Nanomaterials could be the answer to bettering the quality of oocytes, which is essential for IVF success.To achieve this, on-chip manipulation of culture medium microdroplets and electrical stimulation of embryos and gametes have displayed encouraging results in a study conducted by Karcz et al (2023). Additionally, Morimoto et al (2023) found that mitochondrial transfer to human oocytes leads to acceptable clinical outcomes, enhancing embryo quality.…”
Section: Applications Of Nanomaterials In In Vitro Fertilization (Ivf)mentioning
confidence: 99%
See 1 more Smart Citation
“…В животноводстве для получения и сохранения высококачественных женских гамет широко применяют вспомогательные репродуктивные технологии (ВРТ). Цикл ВРТ включает извлечение ооцитов, созревание in vitro (IVM), экстракорпоральное оплодотворение (ЭКО) или интрацитоплазматическую инъекцию сперматозоидов (ИКСИ), трансплантацию эмбрионов (ТЭ), а также криоконсервацию гамет или эмбрионов [1]. Криоконсервация -уникальный метод для сохранения половых клеток различных видов млекопитающих, ценных пород сельскохозяйственных животных в условиях стремительного снижения биоразнообразия.…”
Section: Introductionunclassified
“…Microfluidics is a rapidly growing field that involves the manipulation of small volumes of fluids in microscale channels, offering precise control over the cellular microenvironment ( Whitesides, 2006 ), superior nutrient and waste exchange ( Berthier et al, 2012 ), and the potential for high-throughput screening ( Sackmann et al, 2014 ). This technology has been increasingly applied to various aspects of IVEP, including oocyte and sperm handling ( Beckham et al, 2018 ; Wagenaar et al, 2015 ; El-Sherry et al, 2014 ; Scherr et al, 2015 ), in vitro fertilization (IVF) ( Clark et al, 2005 ; Huang et al, 2018 ; Suh et al, 2006 ), and embryo culture and assessment ( Esteves et al, 2013 ; Huang et al, 2015 ; Karcz et al, 2023 ; Kieslinger et al, 2015 ; Kim et al, 2009 ). 3D culture systems, on the other hand, provide a more physiologically relevant environment for cell growth and differentiation compared to traditional 2D culture systems ( Baker and Chen, 2012 ).…”
Section: Introductionmentioning
confidence: 99%